2015
DOI: 10.1515/bvip-2015-0054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the ageing process on the intensity of post mortem proteolysis and tenderness of beef from crossbreeds

Abstract: The aim of the study was the evaluation of the effect of ageing on the extent of myofibrillar proteins degradation and tenderness of beef in different crossbreeds, BB × HF and SM × HF, from which the musculus semitendinosus was obtained. The pH value, basic composition of meat, and colour parameters were determined on the 3 rd d post mortem. The Warner Bratzler shear force and the extent of protein degradation were evaluated in regard to the effect of ageing time. Meat of BB × HF crossbreed had a lower amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…By electrophoretic separation of muscle proteins and the use of monoclonal antibodies for specifically tracking troponin T, it was proved that troponin T significantly decreased with aging time ( p < .001), as presented in Table . The results obtained concur with earlier studies by Sun et al () and Moczkowska, Półtorak, and Wierzbicka (). The most significant drop in the level of troponin T occurred in both ST and PM from the 2nd to 7th days of aging, when the activity decreased by 17.30 and 20.42%, respectively.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…By electrophoretic separation of muscle proteins and the use of monoclonal antibodies for specifically tracking troponin T, it was proved that troponin T significantly decreased with aging time ( p < .001), as presented in Table . The results obtained concur with earlier studies by Sun et al () and Moczkowska, Półtorak, and Wierzbicka (). The most significant drop in the level of troponin T occurred in both ST and PM from the 2nd to 7th days of aging, when the activity decreased by 17.30 and 20.42%, respectively.…”
Section: Resultssupporting
confidence: 93%
“…By electrophoretic separation of muscle proteins and the use of monoclonal antibodies for specifically tracking troponin T, it was proved that troponin T significantly decreased with aging time (p < .001), as presented in Table 3. The results obtained concur with earlier studies by Sun et al (2014) and Moczkowska, P ołtorak, and Wierzbicka (2015).…”
Section: Impact Of Troponin T Degradation On Shear Forcesupporting
confidence: 93%
“…() who also showed strong positive correlation ( r > 0.75, P < 0.01). The decrease in desmin and Tn‐T and increase in polypeptides: 30 and 46 kDa in all analysed muscles (but at varying rates) indicated that the postmortem proteolysis of myofibrillar proteins is strictly related to the ageing process, which is in agreement to previous studies (Huff Lonergan et al ., ; Moczkowska et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The measurement of the shear force value was performed with Instron 5965 (Instron, Norwood, USA), equipped with a 500 N head, Warner-Bratzler measurement unit, and Bluehill® 2 software. Knife speed of 200 mm·min -1 was used for measurement purposes (16).…”
Section: Methodsmentioning
confidence: 99%